Pengaruh Parent Autonomy Support terhadap School Engagement pada Siswa Kelas IV-VI SD â€œXâ€ di Kota Bandung - Clarissa Devina; Jane Savitri; Destalya Anggrainy Mogot Pandin (Universitas Kristen Maranatha, 2017)
261 students participated in this research. Questionnaire of Parent Autonomy Support based on the theory of Grolnickâ€™s Parental Autonomy Support (2003) with reliability score of r = 0.714. The research also involved the use of Questionnaire of School Engagement based on Fredricks, Blumenfeld, and Parisâ€™s theory (2004). Moreover, calculation factor analysis is performed using Confirmatory Factor Analysis (CFA). Based on the result, it is revealed that Parental Autonomy Support significantly affects school engagement (F = 33,637, rÂ² = 0,115, Ï < 0,01). It also significantly affects the three components of school engagement, namely behavioral engagement (Î² = 0,235, rÂ² = 0,055, Ï < 0,01), emotional engagement (Î² = 0,305, rÂ² = 0,093, Ï < 0,01), and cognitive engagement (Î² = 0,317, rÂ² = 0,100, Ï < 0,01). As a conclusion, Parental Autonomy Support gives an influence towards school engagement and its components. It is also advised that the school can create Psychoeducation for parents to develop their Parent Autonomy Support.Â Keywords: parent autonomy support, school engagement, 4-6 grade elementary school students